Collateral eligibility of corporate debt in the Eurosystem - Loriana Pelizzon; Max Riedel; Zorka Simon; Marti G. Subrahmanyam (Leibniz Institute for Financial Research SAFE, 2020)
We study how the Eurosystem Collateral Framework for corporate bonds helps the European Central Bank (ECB) fulfill its policy mandate. Using the ECBs eligibility list, we identify the first inclusion date of both bonds and issuers. We find that due to the increased supply and demand for pledgeable collateral following eligibility, (i) securities lending market trading activity increases, (ii) eligible bonds have lower yields, and (iii) the liquidity of newly-issued bonds declines, whereas the liquidity of older bonds is una↵ected/improves. Corporate bond lending relaxes the constraint of limited collateral supply, thereby making the market more cohesive and complete. Following eligibility, bond-issuing firms reduce bank debt and expand corporate bond issuance, thus increasing overall debt size and extending maturity.
Keywords: G12; G14; G32; E58; 330; Collateral Policy; ECB; Corporate Bonds; Corporate Debt Structure; Eligibility premium